2018
DOI: 10.21276/ijcmr.2018.5.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Strabismus at a Tertiary Care Hospital in Kashmir

Abstract: Introduction: Strabismus is a state of abnormal alignment of the two eyes. Current research was aimed at studying the profile of strabismus at a tertiary care hospital in Kashmir valley. Material and methods: Strabismus patients attending squint clinic of a tertiary care referral centre in Kashmir, between December, 2015 and December, 2017, across all age groups were included in this study. Patients operated previously for strabismus were excluded. Visual acuity, cycloplegic retinoscopy, stereopsis assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Our study results also portrayed a prevalence of 0.6% (n = 67) cases of uveitis, satisfying the results of the former studies. www.journals.viamedica.pl/ophthalmology_journal Sarosh et al 2018, in their 2-year study period, found 45.9% from 0-10 years and 29% within the age ranged from 10-20 years with a squint, of which esotropia was highly prevalent in approximately 60% [64]. In our study 1.2% of patients (n = 143) were diagnosed with ocular deviations.…”
Section: Discussionsupporting
confidence: 44%
“…Our study results also portrayed a prevalence of 0.6% (n = 67) cases of uveitis, satisfying the results of the former studies. www.journals.viamedica.pl/ophthalmology_journal Sarosh et al 2018, in their 2-year study period, found 45.9% from 0-10 years and 29% within the age ranged from 10-20 years with a squint, of which esotropia was highly prevalent in approximately 60% [64]. In our study 1.2% of patients (n = 143) were diagnosed with ocular deviations.…”
Section: Discussionsupporting
confidence: 44%
“…Rimsha Sarosh et al study showed 59.93% had esotropia, 36.6% had exotropia. 9 Similarly in Mohney BG et al esotropia is the most common form in the first six years of life; beyond this age exotropia predominates. 10 In all these study different age group was considered and the age of onset cannot be determined as the history obtained from parents becomes the only source and by itself is not very accurate.…”
Section: Discussionmentioning
confidence: 88%
“…Tarakeswara Rao Attada et al study 14.7% had intermittent exotropia, Rimsha Sarosh et al study 37.17% had intermittent exotropia. 7,9 There is an inexplicable superstitious belief in the study population that strabismus brings good luck to the family of these children. So the parents of boys were unwilling to let their children undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors concluded that strabismus is associated with a worse quality of life. Sarosh et al (2018) observed that children with visual impairments spent most of their play time alone and that peer perceptions of these children are that themselves are less capable, less desirable as friends and peers, in greater need of help, and less popular than other students. Therefore, they are in a situation of greater social vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…These social circumstances influence the inter and intrapersonal relationships of children with ocular pathology at family, school and social levels, forcing them to face stressful social situations in their relationship with their peers, teachers and family (Sánchez-Caballero, 2015;Sarosh et al, 2018). Alshehri (2016) points out that stressful situations can also appear in the mothers of children with strabismus and in some cases even lead to the appearance of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%